La identità del giurista nell’era digitale. Il ruolo della filosofia del diritto - Favaro, Andrea (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The contribution presents some critical observations in order to the claim to recognize the “rule” of the technologies in order a renewed identity of the role of the jurist. Highlighting the vagueness of the notion of “legal informatic” and its actual dimension, the Author recovers some paradigms of juridical and political theory to recognize a renewed importance of the critical thought. The contribution makes an attempt to analyze the formative function of the philosophy of law with the aim of recognizing the roots of this relationship.